2008
DOI: 10.1530/eje-07-0796
|View full text |Cite
|
Sign up to set email alerts
|

Retinol, retinol-binding protein 4, abdominal fat mass, peak bone mineral density, and markers of bone metabolism in men: the Northern Osteoporosis and Obesity (NO2) Study

Abstract: Context: The association between retinol and bone mineral density (BMD) in males after puberty has not been fully investigated previously. Objective: To investigate the association between retinol, retinol-binding protein-4 (RBP-4), BMD (g/cm 2 ), abdominal fat mass, and markers of bone metabolism in young men. Design: Longitudinal study. Participants: Seventy-eight healthy males with a mean age of 22.6G0.7 years at baseline. A follow-up was conducted in 73 of the participants 2.0G0.4 years later. Main outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…The concentrations are similar to those observed in women in the US and Europe (15)(16)(17)34) but somewhat lower than those reported for Swedish men (13,20). Also, the urinary cadmium concentrations were in the range of those observed in women of a similar age in the US and Europe (6,7,35,36).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The concentrations are similar to those observed in women in the US and Europe (15)(16)(17)34) but somewhat lower than those reported for Swedish men (13,20). Also, the urinary cadmium concentrations were in the range of those observed in women of a similar age in the US and Europe (6,7,35,36).…”
Section: Discussionsupporting
confidence: 74%
“…Null or weak associations have previously been observed for serum retinol or retinyl esters in relation to BMD or fracture risk (15)(16)(17)(18)20,(37)(38)(39). Some studies have found retinol to be associated with higher BMD or have shown that women with osteoporosis have lower retinol concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context a possible role for adipokines (leptin and adiponectin) [49], fetuin-A [50], and retinol-binding protein 4 [51] has been identified.…”
Section: Bone Structure/strength/turnover and Qualitymentioning
confidence: 99%
“…Evidence includes the negative association between osteocalcin (a bone formation marker) and retinol [11], the association between carotenoid intake and loss of bone mineral density [12], and the in vitro, animal, and human evidence suggesting a unique anabolic effect on bone calcification and osteoporosis prevention of β-cryptoxanthin [13]. Additionally, high oxidative stress is associated with reduced BMD and bone metabolism markers in hypercholesterolemic subjects [14] and elderly men [15], and serum α-tocopherol levels seem to modify the association between urinary 8-iso-PGF2α and BMD in the elderly [15].…”
Section: Introductionmentioning
confidence: 99%